A new felt scale genus Macroporicoccus gen. n. (Hemiptera: Coccoidea: Eriococcidae) from China, with a redescription of Macroporicoccus ulmi (Tang & Hao) comb. n. - Nan, Nan; Deng, Jun; Wu, San’an (Zootaxa, 2013)
The Chinese species Cryptococcus ulmi Tang & Hao is found to be distantly related to other sampled Cryptococcus species based on both molecular and morphological study. A new felt scale genus, Macroporicoccus Nan & Wu gen. n., is erected therefore for C. ulmi. The new genus differs from other eriococcid genera due to the presence of large simple pores, here referred to as macrodisc pores. The adult female of Macroporicoccus ulmi (Tang & Hao) comb. n. is redescribed and illustrated. Some important taxonomic characters are illustrated with SEM photographs.